TEMPERATURE CHANGE OVER TIME IN A LAYER OF RAW COTTON DURING THE DRYING PROCESS - Akhmedov. A, Djunayeva. L.A. (Confrencea, 2022)
Scientific research is being carried out around the world aimed at improving the accuracy and speed of cotton moisture control devices and expanding their functionality. Research into the development and improvement of instruments that provide high accuracy, sensitivity, speed and improved metrological characteristics in monitoring the moisture content of cotton is becoming increasingly important.